Evaluación de una Vacuna Parasitaria (Cooperia curticei) en Ovinos. - Murillo Mena, Davis Steven (2023)
In Ecuador, its presence Cooperia curticei has been recorded in tropical, subtropical, and inter-Andean environments. Due to its altitude of 3000 meters above sea level, the Highlands region has more presence of Cooperia spp, with 29% more prevalence than other regions. This nematode causes the death of sheep. This project aims was to evaluate the parasitic vaccine for Cooperia Curticei in the sheep located in the Cusualo area, parish of Zumbahua, canton of Pujili, province of Cotopaxi, to benefit all producers by avoiding a technical, environmental, and economic impact. This vaccine was assessed through serological IgA and IgE tests and hematological and stool tests to establish its efficacy. Samples from 30 sheep were evaluated in the laboratory of the UTC’s Veterinary Clinic on the Salache campus, using flotation techniques with sucrose solution. The same procedure was followed for identifying Cooperia curticei eggs and estimating the load. Post-inoculation results showed a 92% decrease in eggs per field. The results of post-inoculation immunochemistry E were obtained in 55% of the sheep, with normal reference values (NRF). The other 45% obtained low and high levels of NRF. The results of immunochemistry A showed that 50% of the sheep had normal values, and 50% had high and low levels of NRF. The red blood cell count showed thrombocytopenia and anemia in the sheep sampled. In conclusion, the presence of Cooperia curticei was determined even after inoculation, without distinction of age and sex. This experiment reduced possible economic expenses in deaths, weight loss, and veterinary drug costs.